From the reprise overture to Liszt’s B minor Sonata. Romantic creations in an eighteenth century formal ‘corset’? - Ryszka-Komarnicka, Anna (Interdisciplinary Studies in Musicology, 2018)
The present paper summarises the general affinities that link the great romantic piano fantasies (Schubert’s Op. 15, Schumann’s Op. 17, Chopin’s Op. 49 and Liszt’s B minor Sonata) by means of the presence of dual structures of various kinds, including the tonal, formal and an extramusical, interpretational ‘false bottom’, the latest often of autobiographical nature. One of the most prominent dual structures present in all the above mentioned fantasies is a so-called ‘duble-function form’ (apart from far-reaching individualism in detailed solutions) which have no roots in the tradition of keyboard fantasia written by predecessors. As possible source of inspiration some oeuvres of Beethoven are often evoked. However, the paper juxtaposes them with the tradition of the so-called reprise overture, a particular kind of sonata form (called also ‘interpolated sonata form’ as its key element consists in an intrusion of slow movement within the course of sonata form) that emerged in the circles of Italian 18th century opera, widespread often in conjunction with the scope to link an operatic sinfonia with the rest of the drama. Examples by Salieri, Mozart and Haydn are briefly analyzed to show the variety of solutions and posing the hypothesis that reprise overture might be (as transferred well into the 19th century by many operatic composers and ‘kleine Meisters’ that used it in purely instrumental pieces) one of the possible - and unexpected - roots of the formal design of the greatest oeuvres in piano literature ever composed.